Golf balls
The golf ball design with a hydrophobic outer layer and urethane paint additives addresses the issue of reduced flight distance and mud adherence in rainy weather by enhancing water repellency and reducing air resistance, thereby maintaining performance.
Patent Information
- Application Number
- JP2020167832
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-25
- Filing Date
- 2020-10-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-10-02
AI Technical Summary
Golf balls with hydrophobic surfaces having a contact angle of 90° or more experience reduced flight distance in rainy weather due to increased air resistance and adherence of mud and foreign substances, which are not effectively removed.
A golf ball design featuring a core, cover, and an outer surface layer with a contact angle of 90° or more, a dynamic contact angle of 85° or less, and adhesive strength of 130 μN or less, using a urethane paint with water-repellent additives like silicone resin and acrylic additives, to enhance water repellency and reduce mud adhesion.
The design prevents significant reduction in flight distance and effectively removes mud, maintaining performance in rainy conditions by ensuring low air resistance and easy detachment of adhered substances.
Smart Images

Figure 0007623121000004 
Figure 0007623121000005 
Figure 0007623121000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a golf ball, and more particularly to a golf ball having high water repellency.
[0002] Golf is played even in rainy weather, but compared to sunny weather, the surface of the golf ball becomes wet and the air resistance increases, which causes a problem of reduced carry distance when hit with a driver. Therefore, for example, Japanese Patent Laid-Open Publication No. 6-114125 describes a golf ball having an outer surface made of a water-repellent material with a contact angle of 90° or more, such as a fluorine-based polymer or silicone resin.
[0003] Furthermore, Japanese Patent Application Laid-Open No. 2001-214131 describes the use of a urethane resin containing an organosilicon compound as a clear paint for the surface of a golf ball, in order to make it easier to remove dirt from the surface of the golf ball, and to make the contact angle of the surface 90° or more.
[0004] JP 2014-527222 A describes reducing the surface energy in a soft surface coating for a golf ball, thereby reducing the coefficient of friction of the surface of the golf ball. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-114125 [Patent Document 2] JP 2001-214131 A [Patent Document 3] JP 2014-527222 A Summary of the Invention [Problem to be solved by the invention]
[0006] Thus, it is said that by making the surface of a golf ball hydrophobic, i.e., by making the contact angle 90° or more, it is possible to prevent a decrease in the flight distance of driver shots, especially when playing in the rain, and to prevent the adhesion of mud and other foreign matter to the surface of the golf ball. However, even in the case of a water-repellent golf ball with a contact angle of 90° or more, there are cases in which mud and other foreign matter that has adhered to the surface of the golf ball is not removed and remains in large quantities, and therefore there is a demand for further improved performance in preventing the adhesion of mud and other foreign matter.
[0007] In view of the above problems, the present invention aims to provide a golf ball that can prevent a decrease in the carry distance of driver shots when playing in the rain, and can more reliably prevent the adhesion of mud and the like to the surface of the golf ball. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the golf ball of the present invention comprises a core, a cover disposed on the outside of the core and having dimples formed thereon, and an outer surface layer disposed on the entire outside surface of the cover, the outer surface layer being formed from a material having a contact angle of 90° or more, a dynamic contact angle of 85° or less, and an adhesive strength of 130 μN or less, more preferably 110 μN or less, and the material forming the outer surface layer includes a urethane paint containing a water-repellent additive.
[0009] The golf ball preferably has a dynamic friction coefficient of 0.48 or less. The cover is preferably made of a material having a Shore D hardness of 48 or more. The outer surface layer preferably has a thickness of 8 to 20 μm.
[0010] The water-repellent additive may include silicone resin, silicone oil, silicone rubber, an acrylic additive, or a combination thereof. The silicone oil may include methyl hydrogen silicone oil or dimethyl silicone oil. The acrylic additive may include silicone modified acrylate. Since the acrylic additive is less likely to lower the surface tension than silicon, it is possible to impart uniform water repellency to the entire ball. The amount of the water-repellent additive may be 0.15 to 5.00% by mass based on the total amount of the base material including the solvent.
[0011] The urethane coating may contain a polyisocyanate as a curing agent, and the polyisocyanate may contain both an adduct and an isocyanurate of hexamethylene diisocyanate. The mixing ratio of the isocyanurate of hexamethylene diisocyanate and the adduct (isocyanurate / adduct) may be 95 / 5 to 40 / 60 by mass ratio. The urethane coating may contain a polyol and a solvent as a base agent, and the polyol may contain a polyester polyol. Effect of the Invention
[0012] According to the present invention, when the outer surface layer is formed from a material with a contact angle of 90° or more, the surface of the golf ball becomes water-repellent, preventing a decrease in the driver's carry distance when playing in the rain. In addition, since the dynamic contact angle (also called the sliding angle) of the material is 85° or less and the adhesive strength is 130 μN or less, more preferably 110 μN or less, water droplets and mud adhering to the surface of the golf ball are easily able to slide off, thereby more reliably preventing the adhesion of solid components such as mud.
[0013] In particular, high spin performance can be achieved by using polyisocyanate as a curing agent for urethane paint, and using two types of hexamethylene diisocyanate (HMDI) as this polyisocyanate: an adduct with excellent flexibility and a nurate with comparatively high toughness. In addition, by lowering the dynamic friction coefficient of the golf ball to 0.48 or less, the spin rate on driver shots on sunny days is good, and the driving distance on sunny days can be increased. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view illustrating an embodiment of a golf ball according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a measuring device for the dynamic friction coefficient of a golf ball according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating the dynamic contact angle of the golf ball according to the present invention. [Figure 4] 1 is a schematic diagram showing an adhesive force measuring device for a golf ball according to the present invention. [Diagram 5] 5 is a photograph showing the results of a mud adhesion test on the surface of a golf ball in an example according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of a golf ball according to the present invention will be described with reference to the accompanying drawings.
[0016] As shown in FIG. 1, the golf ball 1 of the present embodiment mainly comprises a core 10 located at the center of the ball, a cover 20 surrounding the outer periphery of the core 10, and an outer surface layer 30 surrounding the outside of the cover. A plurality of dimples 22 are formed on the surface of the cover 20. The outer surface layer 30 covers the entire surface of the cover 20 with a substantially uniform thickness along the depressions of the dimples 22. Note that in the present embodiment, a golf ball having a two-layer structure of a core and a cover will be described, but the present invention is not limited thereto, and the golf ball may have an intermediate layer between the core 10 and the cover 20, a multi-layer core of two or more layers, or a multi-layer structure of three or more layers.
[0017] The core 10 can be mainly formed of a base rubber. As the base rubber, a wide variety of rubbers (thermosetting elastomers) can be used, such as polybutadiene rubber (BR), styrene butadiene rubber (SBR), natural rubber (NR), polyisoprene rubber (IR), polyurethane rubber (PU), butyl rubber (IIR), vinyl polybutadiene rubber (VBR), ethylene propylene rubber (EPDM), nitrile rubber (NBR), and silicone rubber, but are not limited thereto. As the polybutadiene rubber (BR), for example, 1,2-polybutadiene, cis-1,4-polybutadiene, etc. can be used.
[0018] In addition to the base rubber that is the main component, for example, a co-crosslinking agent, a crosslinking agent, a filler, an antioxidant, an isomerizing agent, a mastication accelerator, sulfur, and an organic sulfur compound can be added arbitrarily to the core 10. Also, instead of the base rubber, a thermoplastic elastomer, an ionomer resin, or a mixture thereof can be used as the main component.
[0019] The core 10 has a substantially spherical shape. The outer diameter of the core 10 is preferably about 42 mm or less as an upper limit, more preferably about 41 mm or less, and even more preferably about 40 mm or less. The outer diameter of the core 10 is preferably about 5 mm or more as a lower limit, more preferably about 15 mm or more, and most preferably about 25 mm or more. The core 10 is shown in FIG. 1 as a solid core, but is not limited thereto and may be a hollow core. The core 10 is shown in FIG. 1 as a single layer, but is not limited thereto and may be a core consisting of multiple layers, such as a center core and a surrounding layer.
[0020] The core 10 can be molded by a known method for molding a golf ball core. For example, but not limited to, a material containing a base rubber is kneaded in a kneading machine, and then the kneaded mixture is pressure-vulcanized and molded in a round mold to obtain a core having multiple layers. A known method for molding a multi-layered solid core can be used to mold a core having multiple layers. For example, a center core is obtained by kneading a material in a kneading machine and pressure-vulcanizing and molding the kneaded mixture in a round mold, and then a material is kneaded in a kneading machine as an envelope layer, and the kneaded mixture is molded into a sheet, and the sheet is used to cover the center core, and then the sheet is pressure-vulcanized and molded in a round mold to obtain a multi-layered core.
[0021] The cover 20 may be formed using, but is not limited to, a thermoplastic polyurethane, an ionomer resin, or a mixture thereof.
[0022] The structure of the thermoplastic polyurethane material is composed of a soft segment made of a polymer polyol (polymeric glycol) and a chain extender and a polyisocyanate constituting a hard segment. Here, the polymer polyol used as the raw material is not particularly limited, but in the present invention, polyester-based polyols and polyether-based polyols are preferred. Specific examples of polyester-based polyols include adipate-based polyols such as polyethylene adipate glycol, polypropylene adipate glycol, polybutadiene adipate glycol, and polyhexamethylene adipate glycol, and lactone-based polyols such as polycaprolactone polyol. Examples of polyether polyols include poly(ethylene glycol), poly(propylene glycol), and poly(tetramethylene glycol).
[0023] The chain extender is not particularly limited, but in the present invention, a low molecular weight compound having two or more active hydrogen atoms in the molecule capable of reacting with an isocyanate group and a molecular weight of 2,000 or less can be used, and among these, an aliphatic diol having 2 to 12 carbon atoms is preferred. Specific examples include 1,4-butylene glycol, 1,2-ethylene glycol, 1,3-butanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, and the like, and among these, 1,4-butylene glycol is particularly preferred.
[0024] The polyisocyanate compound is not particularly limited, but in the present invention, for example, one or more compounds selected from the group consisting of 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, naphthylene 1,5-diisocyanate, tetramethylxylene diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate can be used. However, depending on the type of isocyanate, it may be difficult to control the crosslinking reaction during injection molding. Therefore, in the present invention, from the viewpoint of the balance between stability during production and the physical properties exhibited, the aromatic diisocyanate 4,4'-diphenylmethane diisocyanate is preferred.
[0025] The ionomer resin may be, but is not limited to, one having the following component (a) and / or component (b) as the base resin. Optionally, the following component (c) may be added to this base resin. The component (a) is an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester ternary random copolymer and / or a metal salt thereof, the component (b) is an olefin-unsaturated carboxylic acid binary random copolymer and / or a metal salt thereof, and the component (c) is a thermoplastic block copolymer having a polyolefin crystalline block and a polyethylene / butylene random copolymer.
[0026] In addition to the main component of the thermoplastic polyurethane or ionomer resin, the cover 20 may contain a thermoplastic resin or elastomer other than the thermoplastic polyurethane. Specifically, one or more of polyester elastomers, polyamide elastomers, ionomer resins, styrene block elastomers, hydrogenated styrene butadiene rubber, styrene-ethylene-butylene-ethylene block copolymers or modified products thereof, ethylene-ethylene-butylene-ethylene block copolymers or modified products thereof, styrene-ethylene-butylene-styrene block copolymers or modified products thereof, ABS resins, polyacetal, polyethylene, and nylon resins may be used. In particular, it is preferable to employ polyester elastomers, polyamide elastomers, and polyacetals, because they maintain good productivity and improve resilience and abrasion resistance by reacting with isocyanate groups. When the above components are blended, the blending amount is appropriately selected depending on the adjustment of the hardness of the cover material, the improvement of the resilience, the improvement of the fluidity, the improvement of the adhesion, etc., and is not particularly limited, but is preferably 5 parts by mass or more per 100 parts by mass of the thermoplastic polyurethane component. In addition, the upper limit of the blending amount is also not particularly limited, but is preferably 100 parts by mass or less, more preferably 75 parts by mass or less, and even more preferably 50 parts by mass or less per 100 parts by mass of the thermoplastic polyurethane component. In addition, polyisocyanate compounds, fatty acids or derivatives thereof, basic inorganic metal compounds, fillers, etc. may be added.
[0027] The thickness of the cover 20 is not limited to this value, but the lower limit is preferably about 0.2 mm or more, and more preferably about 0.4 mm or more. The upper limit of the thickness of the cover 20 is preferably about 4 mm or less, more preferably about 3 mm or less, and even more preferably about 2 mm or less. A plurality of dimples 22 are formed on the surface of the cover 20. The size, shape, number, etc. of the dimples 22 can be designed as appropriate depending on the desired aerodynamic characteristics of the golf ball 1.
[0028] The hardness of the cover 20 is not limited to, but the lower limit is preferably about 48 or more, more preferably about 50 or more, and even more preferably about 53 or more, in Shore D. The upper limit of the hardness of the cover 20 is preferably about 70 or less, more preferably about 68 or less, and even more preferably about 65 or less, in Shore D. The hardness of the cover 20 is measured in accordance with the ASTM D2240-95 standard after the resin material of the cover layer is molded into a sheet having a thickness of 2 mm and allowed to stand for two weeks or more.
[0029] The method for forming the cover 20 can be a known molding method for golf ball covers. For example, but not limited to, the cover 20 is formed by injection molding a material for the cover into a mold. The mold for molding the cover has a cavity for molding the cover, and the wall surface of the cavity has a plurality of protrusions for forming dimples. The core 10 is placed in the center of the cavity, and the cover 20 is formed to cover the core 10.
[0030] An intermediate layer (not shown) may be provided between the core 10 and the cover 20. An intermediate layer having a core-like function may be provided, or an intermediate layer having a cover-like function may be provided. Also, multiple intermediate layers may be provided, for example, multiple intermediate layers having a core-like or cover-like function may be provided, or a first intermediate layer having a core-like function and a second intermediate layer having a cover-like function may be provided.
[0031] The outer surface layer 30 can be formed using, but is not limited to, a urethane paint composed of a polyol as a base agent and a polyisocyanate as a hardener as a main component. A water-repellent additive is added to this main component as an additive so that the material forming the outer surface layer 30 has a contact angle of 90° or more and a dynamic contact angle of 85° or less. Each component is described below.
[0032] The polyol is not limited thereto, but it is preferable to use a polyester polyol, and two kinds of polyester polyols, that is, polyester polyol (A) and polyester polyol (B), may be used. When using these two kinds of polyester polyols, the weight average molecular weights (Mw) are different, and it is preferable that the weight average molecular weight (Mw) of the (A) component is 20,000 to 30,000, and the weight average molecular weight (Mw) of the (B) component is 800 to 1,500. The weight average molecular weight (Mw) of the (A) component is more preferably 22,000 to 29,000, and even more preferably 23,000 to 28,000. The weight average molecular weight (Mw) of the (B) component is more preferably 900 to 1,200, and even more preferably 1,000 to 1,100.
[0033] The polyester polyol is obtained by polycondensation of a polyol and a polybasic acid. Examples of the polyol include diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, hexylene glycol, dimethylolheptane, polyethylene glycol, and polypropylene glycol, triols, tetraols, and polyols having an alicyclic structure. Examples of polybasic acids include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, azelaic acid, and dimer acid, aliphatic unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid, aromatic polyvalent carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid, dicarboxylic acids having an alicyclic structure such as tetrahydrophthalic acid, hexahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and endomethylenetetrahydrophthalic acid, and tris-2-carboxyethyl isocyanurate. In particular, polyester polyols having a cyclic structure introduced into the resin skeleton can be used as the polyester polyol of component (A), and examples thereof include polyester polyols obtained by polycondensation of a polyol having an alicyclic structure such as cyclohexanedimethanol with a polybasic acid, or polycondensation of a polyol having an alicyclic structure with a diol or triol with a polybasic acid. On the other hand, as the polyester polyol of component (B), a polyester polyol having a multi-branched structure can be used, and an example thereof includes polyester polyols having a branched structure such as "NIPPOLAN 800" manufactured by Tosoh Corporation.
[0034] In addition, when the above-mentioned polyester polyol is used, the weight average molecular weight (Mw) of the entire base is preferably 13,000 to 23,000, more preferably 15,000 to 22,000. In addition, the number average molecular weight (Mn) of the entire base is preferably 1,100 to 2,000, more preferably 1,300 to 1,850. If these average molecular weights (Mw and Mn) deviate from the above ranges, the abrasion resistance of the coating film may decrease. The weight average molecular weight (Mw) and the number average molecular weight (Mn) are measured values (polystyrene equivalent values) by gel permeation chromatography (hereinafter abbreviated as GPC) measurement by differential refractometer detection. In the case where two types of polyester polyols are used, the Mw and Mn of the entire base are also within the above-mentioned ranges.
[0035] The blending amounts of the above two types of polyester polyols (A) and (B) are not particularly limited, but it is preferable that the blending amount of the (A) component is 20 to 30 mass % based on the total amount of the base material including the solvent, and the blending amount of the (B) component is 2 to 18 mass % based on the total amount of the base material.
[0036] The polyisocyanate is not particularly limited, but may be a commonly used aromatic, aliphatic, alicyclic, or other polyisocyanate, specifically, tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, 1,4-cyclohexylene diisocyanate, naphthalene diisocyanate, trimethylhexamethylene diisocyanate, dicyclohexylmethane diisocyanate, 1-isocyanato-3,3,5-trimethyl-4-isocyanatomethylcyclohexane, etc. These may be used alone or in combination.
[0037] Examples of the modified hexamethylene diisocyanate include polyester modified hexamethylene diisocyanate and urethane modified hexamethylene diisocyanate. Examples of the derivatives of hexamethylene diisocyanate include nurate (isocyanurate), biuret, and adduct of hexamethylene diisocyanate (HMDI). The adduct refers to an adduct of diisocyanate and trimethylolpropane. The nurate refers to a trimer of diisocyanate. In particular, high spin performance can be obtained by using two types of HMDI, an adduct with excellent flexibility and a nurate with relatively high toughness. Examples of HMDI nurates include those under the trade names Coronate 2357 (manufactured by Tosoh Corporation), Sumidur N3300 (manufactured by Sumika Covestro Urethanes), Duranate TPA-100 (manufactured by Asahi Kasei Corporation), Takenate D170N, Takenate D177N (both manufactured by Mitsui Chemicals), and Burnock DN-980 (manufactured by DIC Corporation). Examples of HMDI adducts include those under the trade names Coronate HL (manufactured by Tosoh Corporation), Takenate D160N (manufactured by Mitsui Chemicals), Duranate E402-80B, Duranate E405-70B (both manufactured by Asahi Kasei Corporation), Burnock DN-955, and Burnock DN-955S (both manufactured by DIC Corporation). The mixing ratio of the isocyanurate to the adduct (isocyanurate / adduct) is preferably from 95 / 5 to 40 / 60, more preferably from 80 / 20 to 55 / 45, in mass ratio.
[0038] In the urethane coating material made of polyol and polyisocyanate, which are the main components of the outer surface layer 30, the molar ratio (NCO group / OH group) of the hydroxyl group (OH group) of the polyol to the isocyanate group (NCO group) of the polyisocyanate is preferably 0.6 or more, more preferably 0.65 or more. The upper limit of this molar ratio is preferably 1.5 or less, more preferably 1.0 or less, and even more preferably 0.9 or less. If this molar ratio is below the lower limit, unreacted hydroxyl groups may remain, which may deteriorate the performance and water resistance of the coating film for golf balls. On the other hand, if the molar ratio exceeds the upper limit, the isocyanate groups become excessive, which may react with moisture to produce urea groups (brittle), which may result in a deterioration in the performance of the coating film for golf balls.
[0039] As the curing catalyst (organometallic compound) that promotes the reaction between polyol and polyisocyanate, an amine catalyst or an organometallic catalyst can be used. As this organometallic compound, metal soaps such as aluminum, nickel, zinc, tin, etc., which have traditionally been blended as curing agents in two-component curing urethane paints, can be suitably used.
[0040] The polyol, which is the main agent, and the polyisocyanate, which is the curing agent, can be mixed with various organic solvents depending on the coating conditions. Examples of such organic solvents include aromatic solvents such as toluene, xylene, and ethylbenzene, ester solvents such as ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, and propylene glycol methyl ether propionate, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ether solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and dipropylene glycol dimethyl ether, alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane, and petroleum hydrocarbon solvents such as mineral spirits.
[0041] The water-repellent additive may be, but is not limited to, silicone resin, fluorine-based polymer, silicone oil, silicone rubber, acrylic additive, or a combination thereof. In particular, one that has both water repellency and slippage is preferable. The silicone resin may be, but is not limited to, organic modified polysiloxane (trade name BYK370 or BYK375). The acrylic additive may be, for example, silicone modified acrylate. Silicone modified acrylate is a surface conditioner that incorporates an acrylic structure and a silicone structure in one molecule. Unlike ordinary polyrotaxane-based silicone, the acrylic skeleton has a polysiloxane chain, so that even if the amount of addition is increased, it is difficult to slip, and water repellency can be increased. The silicone modified acrylate may be, for example, BYK3550 or BYK3700 (both manufactured by BYK-Chemie). The silicone oil may be, for example, methyl hydrogen silicone oil or dimethyl silicone oil. The fluorine polymer may be, but is not limited to, tetrafluoroethylene or polytetrafluoroethylene.
[0042] The water-repellent additive is preferably added to the base material. The blending amount of the water-repellent additive is an amount that allows the material forming the outer surface layer 30 to have a contact angle of 90° or more, a dynamic contact angle of 85° or less, and an adhesive strength of 130 μN or less, and is, for example, preferably 0.05% by mass or more as a lower limit, more preferably 0.10% by mass or more, and preferably 10% by mass or less as an upper limit, more preferably 5% by mass or less, based on the total amount of the base material.
[0043] The lower limit of the contact angle is preferably 95° or more, and more preferably 100° or more. On the other hand, if the contact angle is too large, the adhesion between the outer surface layer and the cover decreases, and the outer surface layer tends to be difficult to adhere to the cover or to peel off easily, so the upper limit is preferably 160° or less, and more preferably 150° or less. The contact angle is measured by dropping a 5 μL water drop onto a resin sheet formed with a material to a film thickness of 15 μm, and measuring with a contact angle meter. The contact angle can also be measured on a golf ball manufactured by forming an outer surface layer. In this case, the water drop is dropped on the edge part of the dimple of the golf ball and measured, so that a contact angle equivalent to the above measurement method can be measured.
[0044] The dynamic contact angle is preferably 80° or less as an upper limit, more preferably 75° or less, and is preferably 60° or more as a lower limit, more preferably 65° or more. The dynamic contact angle is measured by dropping a 5 μL water droplet onto a resin sheet formed to a thickness of 15 μm by applying a material, tilting this resin sheet 51 so that the tilt angle α0 with respect to the horizontal gradually increases, and measuring the tilt angle α0 when the water droplet 52 slides down, as shown in the conceptual diagram of FIG. 3. It is also possible to measure the dynamic contact angle on a golf ball manufactured by forming an outer surface layer. In this case, the water droplet is dropped on the edge of a dimple on the golf ball, and the golf ball is tilted, whereby a dynamic contact angle equivalent to that measured by the above-mentioned measuring method can be measured.
[0045] Thus, the contact angle is also called the static contact angle, and it is believed that the more the contact angle is 90° or more and the rounder the water droplets are, the better the water repellency is, but according to the knowledge of the present inventors, this index is not an index of the removal performance of things like mud, which have components significantly different from those of pure water. The dynamic contact angle is also called the sliding angle, and is used as a method for evaluating the oil repellency of the surface of a frying pan, but according to the knowledge of the present inventors, this dynamic contact angle is effective as an index of the removal performance of mud on the surface of a golf ball, and so it was decided to form an outer surface layer 30 that is excellent not only in the contact angle but also in the dynamic contact angle.
[0046] The outer surface layer 30 is formed of a material having an adhesive force of 130 μN or less. The adhesive force is the force required to separate two contacting surfaces of a material. The adhesive force can be measured by a surface force measuring device manufactured by Elionix, which is called ESF-5000Plus. The adhesive force can be measured by contacting a spherical probe 64 fixed to the bottom end of a vertically displaceable measuring element 63 with the surface of a sample 61 of the material to be measured placed on a stage 62, as shown in FIG. 4, and then gradually applying a load to displace the measuring element 63 upward, and measuring the displacement and load when the probe 64 is separated from the surface of the sample 61 with a displacement meter 65 and a load meter (not shown). The absolute value of this load is the adhesive force. It is to be noted that the adhesive force of the material of the outer surface layer can be measured by directly measuring a golf ball on which the outer surface layer is formed, instead of the above-mentioned sample, with the above-mentioned device. In this case, the land portion between the dimples 22 of the golf ball 1 is measured. The number of samples is 5, and the average value is the adhesive force of the outer surface layer 30.
[0047] By forming the outer surface layer 30 from a material having an adhesive strength of 130 μN or less, dirt and the like are less likely to adhere to the surface of the golf ball 1. A more preferable adhesive strength is 120 μN or less. There is no particular limit to the lower limit of the adhesive strength, but a value of 50 μN or more is preferable. If the adhesive strength is less than 50 μN, the amount of spin of the golf ball on approach shots may decrease.
[0048] Furthermore, known paint compounding components may be added, if necessary, to the material forming the outer surface layer 30. Specifically, appropriate amounts of a thickener, an ultraviolet absorbing agent, a fluorescent brightener, a slipping agent, a pigment, etc. may be added.
[0049] The thickness of the outer surface layer 30 is not particularly limited, but is preferably 8 μm or more as a lower limit, more preferably 10 μm or more, and is preferably 22 μm or less as an upper limit, more preferably 20 μm or less. The outer surface layer 30 is shown as one layer in FIG. 1, but is not limited thereto and may be a multi-layer structure of two or more layers. For example, the outer surface layer may have a two-layer structure of an inner layer on the cover side and an outer layer on the outside, the inner layer being a clear layer mainly composed of urethane paint not containing a water-repellent additive, and the outer layer being a water-repellent layer mainly composed of urethane paint containing a water-repellent additive as described above. This is particularly effective when a material with a large contact angle (for example, 140° or more) is used for the outer surface layer as described above.
[0050] The method for forming the outer surface layer 30 on the surface of the cover 20 is not particularly limited, and any known method for painting a golf ball paint on the cover surface can be used, such as an air gun painting method or an electrostatic painting method.
[0051] The golf ball 1 having the outer surface layer 30 formed on the surface of the cover 20 as described above preferably has a dynamic friction coefficient of 0.48 or less. The dynamic friction coefficient can be measured using a contact force tester similar to that described in JP 2013-176530 A, except that in the present invention, as shown in FIG. 2, the golf ball 1 is dropped from a launching section 41 having a height of 90 cm, and is caused to collide with a collision plate 42 inclined at an angle α of 20° with respect to the direction of the drop, and the dynamic friction coefficient at that time is measured by a pressure sensor 43 installed on the collision plate 42. The collision plate angle α is set to 20° based on the image of the face part of an iron club being open during an approach shot. The dynamic friction coefficient is calculated by the following formula. Coefficient of kinetic friction = contact force in the shear direction (Ft(t)) / contact force in the drop direction (Fn(t))
[0052] The upper limit of the kinetic friction coefficient of the golf ball 1 is preferably 0.47 or less, and more preferably 0.46 or less, and the lower limit is preferably 0.36 or more, more preferably 0.38 or more, and even more preferably 0.40 or more.
[0053] The diameter of golf ball 1, according to the rules, has a lower limit of 42.67 mm (1.68 inches) or more, and an upper limit of 44 mm or less is preferable, 43.5 mm or less is more preferable, and 43 mm or less is even more preferable. The weight of golf ball 1, according to the rules, has an upper limit of 45.93 g (1.620 ounces) or less, and a lower limit of 44.5 g or more is preferable, 44.7 g or more is more preferable, and 45.2 g or more is even more preferable. EXAMPLES
[0054] Golf balls having the configurations shown in Tables 1 and 2 were produced and tested to measure the flight distance and spin performance of the golf balls. The blending amounts of the base agent and hardener, which are the materials forming the outer surface layer, in Tables 1 and 2 are expressed in mass % for the base agent and hardener, respectively. Blends A to C of the cover materials shown in Tables 1 and 2 are shown in Table 3. The blending amount of each component in Table 3 is expressed in parts by mass.
[0055] [Table 1]
[0056] [Table 2]
[0057] The main polyol in Tables 1 and 2 was a polyester polyol synthesized by the following method. A reaction apparatus equipped with a reflux condenser, a dropping funnel, a gas inlet tube, and a thermometer was charged with 140 parts by mass of trimethylolpropane, 95 parts by mass of ethylene glycol, 157 parts by mass of adipic acid, and 58 parts by mass of 1,4-cyclohexanedimethanol, and the mixture was heated to 200-240°C with stirring, and heated (reacted) for 5 hours. After that, a polyester polyol with an acid value of 4, a hydroxyl value of 170, and a weight average molecular weight (Mw) of 28,000 was obtained.
[0058] The additives in Tables 1 and 2, i.e., the water-repellent additives, are all commercially available products, with type a being an acrylic additive and type b being a silicone additive, more specifically, type a being a silicone-modified acrylate (manufactured by BYK-Chemie under the trade name BYK3700) and type b being an organically modified polysiloxane (manufactured by BYK-Chemie under the trade name BYK370). In addition, type c was added as a fluorine-based water-repellent agent (a fluorine-based surfactant having a perfluoroalkyl group, with the alkyl group chain length being 7 or less).
[0059] Examples 1 to 2 in Tables 1 to 2 3 and Comparative Example 1 5 As the curing agent, an isocyanate was used, which is a hexamethylene diisocyanate (HMDI) nurate (isocyanurate) product manufactured by Asahi Kasei Corporation, Duranate TPA-100 (NCO content 23.1%, non-volatile content 100%). 2、3 In Comparative Example 1 and Comparative Example 5, the above-mentioned nurate HMDI was used as the isocyanate curing agent, along with Asahi Kasei Corporation's product name Duranate E402-80B (NCO content 7.6%, non-volatile content 80%), which is an adduct of hexamethylene diisocyanate (HMDI). The mixing ratio (mass%) of the nurate and adduct in each example is as shown in Table 2. In each example, a solvent was added to adjust the amount (concentration) of the isocyanate to the total amount of the curing agent including the solvent to the value shown in Tables 1 and 2.
[0060] Butyl acetate was used as the solvent for the base agent, and ethyl acetate and butyl acetate were used as the solvent for the hardener.
[0061] The contact angle was measured by dropping a 5 μL drop of pure water onto a resin sheet formed to a thickness of 15 μm by applying the mixture of the above-mentioned base agent and curing agent, and using a contact angle meter (Model CA-VP, manufactured by Kyowa Interface Science Co., Ltd.). After performing the test under the same conditions, the dynamic contact angle was measured by tilting the resin sheet and measuring the tilt angle α0 of the resin sheet when the water drop slid down.
[0062] The adhesive strength was measured using a surface force measuring device manufactured by Elionix, Inc., under the trade name ESF-5000Plus. The sample used was a resin plate measuring φ30mm x 5mm thick, with a coating layer of 15μm thickness formed over the entire surface. The probe used was a φ1mm glass sphere with a composition of Cr / PDMS / φ1mmBK7, coated with silicone rubber made from PDMS, and then coated with a Cr film of about 3nm by ECR sputtering, with a tip curvature radius of 478μm. The measurement conditions were as follows: Spring constant: 75.755N / m Load step: 1μN / 20ms ·Contact judgment threshold: 20nm / s (PZT rising speed 200nm / s) Number of measurement points: X3 points x Y3 points ·Measurement interval: 200μm
[0063] [Table 3]
[0064] The components used in Table 3 showing the composition of the cover are as follows. T-8195 is a trademarked Pandex thermoplastic polyurethane elastomer manufactured by DIC BayerPolymer. AM7329 is an ionomer resin made by Mitsui DuPont Polychemicals, which is a zinc ion neutralized ethylene-methacrylic acid copolymer. Himilan 1605 is an ionomer resin made by Mitsui DuPont Polychemicals, which is a sodium ion neutralized ethylene-methacrylic acid copolymer. The titanium oxide used is Typeque R-550 manufactured by Ishihara Sangyo Kaisha. The polyethylene wax is manufactured by Sanyo Chemical Industries, Ltd. and is known as Sanwax 161P. Precipitated barium sulfate is manufactured by Sakai Chemical Industry Co., Ltd. under the trade name Precipitated Barium Sulfate 100.
[0065] The core composition was the same in all the examples and comparative examples. The base rubber consisted of 20 parts by weight of polybutadiene A (trade name BR51, manufactured by JSR Corporation), 80 parts by weight of polybutadiene B (trade name BR730, manufactured by JSR Corporation), 39.3 parts by weight of zinc acrylate (manufactured by Wako Pure Chemical Industries Co., Ltd.), 0.6 parts by weight of dicumyl peroxide (trade name Percumyl D, manufactured by Nippon Oil & Fats Co., Ltd.) as an organic peroxide, 0.1 parts by weight of 2,2-methylenebis(4-methyl-6-butylphenol) (trade name Nocrac NS-6, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) as an anti-aging agent, 20.4 parts by weight of zinc oxide (trade name 3-type zinc oxide, manufactured by Sakai Chemical Industry Co., Ltd.), and 1 part by weight of pentachlorothiophenol zinc salt (manufactured by Wako Pure Chemical Industries Co., Ltd.) as an organic sulfur compound. The vulcanization was performed at a temperature of 155°C for 15 minutes. The compounded specific gravity of the core was 1.1702, and the actual specific gravity was 1.1462.
[0066] The dynamic friction coefficient was measured by the contact force tester shown in FIG. 2 described above. The detailed specifications of the contact force tester will be described. The launching part 41 is set to be dropped from a height of 90 cm. The impact plate 42 is composed of a base plate, a surface plate, and a surface material. The base plate is made of steel and has a size of 80 mm×80 mm×15 mm (thickness). The outer surface plate is made of stainless steel (SUS-630) and has a size of 80 mm×80 mm×20 mm. The surface material, which is the outer striking surface, is made of titanium alloy, has no groove shape, has an average roughness Ra: 0.146 μm, a maximum height Ry: 1.132 μm, and has a size of 80 mm×80 mm×10 mm. The pressure sensor 43 installed on the impact plate 42 was a three-component force sensor (model 9067) made by Kistler. The charge amplifier (not shown) was a model 5011B made by Kistler.
[0067] The procedure for measuring the dynamic friction coefficient was as follows. (a) The inclination angle α of the collision plate 42 is adjusted to 20° and fixed. (b) The golf ball 1 is dropped from the launching section 41. (c) The contact force Fn(t) in the falling direction and the contact force Ft(t) in the shear direction when the golf ball 1 collides with the collision plate 42 are measured by the pressure sensor 43, and the maximum value of Ft(t) / Fn(t) is calculated.
[0068] The "distance in rainy weather" in Tables 1 and 2 is the value obtained by measuring the carry distance when hitting a golf ball with a driver (W#1) (TourStageX-Drive415 (loft angle: 10.5°) manufactured by Bridgestone Sports Co., Ltd.) attached to a golf hitting robot on sunny and rainy days and hitting the golf ball with a head speed (HS) of 45 m / s, and subtracting the carry distance on sunny days from the carry distance on rainy days. -4.5 m or less was evaluated as ◎+, -5 m or less was evaluated as ◎, -8 m or less was evaluated as ○, and over -8 m was evaluated as ×. The "W#1 spin amount" in Tables 1 and 2 is the spin amount (rpm) on sunny days measured by an initial condition measuring device ("Science i-Field" manufactured by Bridgestone Sports Co., Ltd.) on the golf ball immediately after hitting. 2850 rpm or less was rated as ◎+, 3000 rpm or less was rated as ◎, 3001 to 3200 rpm or less was rated as ○, and over 3201 rpm was rated as ×. Note that the rainy weather mentioned above refers to a state where the amount of precipitation is 5 mm. Even in rainy weather, the hitting point (the impact point where the club and ball come into contact) was made so that the club and ball were not exposed to rain (so that they did not get wet), and the same hitting conditions were used both in sunny weather and in rainy weather to measure the difference in carry distance.
[0069] The "mud adhesion" in Tables 1 and 2 indicates that 2g of mud was adhered to the surface of a golf ball, and the remaining state of the mud was visually confirmed when the ball was hit under the same conditions as the test for measuring the flying distance by the driver. If the remaining state of the mud was less than 10% of the applied area, it was evaluated as ◎+, if it was less than 20% of the applied area, it was evaluated as ◎, if it was less than 50% of the applied area, it was evaluated as ○, if it was less than 80%, it was evaluated as △, and if it was 80% or more of the applied area, it was evaluated as ×. For reference, a photograph of the state where mud remained on 80% or more of the applied area is shown in FIG. 5A, a photograph of the state where mud remained on less than 20% of the applied area is shown in FIG. 5B, and a photograph of the state where mud remained on less than 80% of the applied area is shown in FIG. 5C.
[0070] As shown in Tables 1 and 2, Examples 1 to 3, in which the outer surface layer was formed from a material with a contact angle of 90° or more, a dynamic contact angle of 85° or less, and an adhesive strength of 130 μN or less, were all able to prevent a significant drop in the driver's flight distance in rainy weather, and also showed excellent removal performance with respect to adhesion of mud. Furthermore, since the dynamic friction coefficient of the golf balls of Examples 1 to 3 was low at 0.48 or less, the spin rate was also good.
[0071] In particular, Example 1, in which the outer surface layer was formed with a material having an adhesive strength of 110 μN or less, was able to prevent the driver's flight distance from decreasing significantly in rainy weather, and also showed a remarkably excellent removal performance with respect to the adhesion of mud. Furthermore, in Examples 2 and 3, by using not only the HMDI in the nurate form but also a mixture of the HMDI in the adduct form, which has excellent flexibility, as the hardening agent, it was possible to increase friction and obtain a higher spin rate.
[0072] On the other hand, even when the contact angle was 90° or more, Comparative Example 1, in which the dynamic contact angle was 90° or more and the adhesive force was greater than 130 μN, was able to prevent a significant drop in the driver's flight distance in rainy weather, but did not obtain sufficient removal performance with respect to the adhesion of mud. Comparative Example 2, in which the dynamic contact angle was 85° or less and the adhesive force was 130 μN or less, but the contact angle was 80°, showed sufficient removal performance with respect to the adhesion of mud, but the flight distance of the driver in rainy weather was significantly reduced. Comparative Example 3, in which the contact angle was 70°, the dynamic contact angle was 90° or more, and the adhesive force was greater than 130 μN, showed a significant drop in the driver's flight distance in rainy weather, and did not obtain sufficient removal performance with respect to the adhesion of mud. Comparative Example 4, which had an adhesive force of 130 μN or less, a contact angle of less than 90°, and a dynamic contact angle of less than 85°, showed sufficient removal performance with respect to mud adhesion, but the spin rate was high, and the driver's flight distance itself in fine weather was slightly reduced, and furthermore, the driver's flight distance in rainy weather was also significantly reduced. Comparative Example 5, which used a mixture of nurate and adduct HMDI as a hardener, had a contact angle of 90° or more, and a dynamic contact angle of 85° or less, so the spin rate was high and it was possible to prevent the driver's flight distance in rainy weather from being significantly reduced, but the adhesive force was greater than 130 μN, so sufficient removal performance with respect to mud adhesion was not obtained. [Explanation of symbols]
[0073] 1 golf ball 10 cores 20 Cover 22 Dimples 30 Outer surface layer 41 Launching section 42 Collision plate 43 Pressure Sensor 51 Test Materials 52 Water drop
Claims
1. A golf ball comprising a core, a cover provided on the outside of the core and having dimples formed thereon, and an outer surface layer provided on the entire outside surface of the cover, wherein the outer surface layer is formed from a material having a contact angle of 90° or more, a dynamic contact angle of 85° or less, and an adhesive strength of 130 μN or less, and the material forming the outer surface layer includes a urethane paint containing a water-repellent additive, the urethane paint includes a polyisocyanate as a curing agent, and the polyisocyanate includes both an adduct and an isocyanurate of hexamethylene diisocyanate.
2. 2. The golf ball according to claim 1, wherein a mixing ratio of the isocyanurate and the adduct of the hexamethylene diisocyanate (isocyanurate / adduct) is from 95 / 5 to 40 / 60 by mass.
3. 3. The golf ball according to claim 1, wherein the coefficient of dynamic friction of the golf ball is 0.48 or less.
4. 4. The golf ball according to claim 1, wherein the cover is made of a material having a Shore D hardness of 48 or more.
5. 5. The golf ball according to claim 1, wherein the outer surface layer has a thickness of 8 to 20 μm.
6. 6. The golf ball according to claim 1, wherein the water repellent additive comprises a silicone resin, a silicone oil, a silicone rubber, an acrylic additive, or a combination thereof.
7. 7. The golf ball according to claim 6, wherein the silicone oil comprises methyl hydrogen silicone oil or dimethyl silicone oil.
8. 7. The golf ball according to claim 6, wherein the acrylic additive comprises a silicone modified acrylate.
9. 9. The golf ball according to claim 1, wherein the amount of the water repellent additive is 0.15 to 5.00% by mass based on the total amount of the base material including the solvent.
10. 10. The golf ball according to claim 1, wherein the urethane paint contains a polyol as a base agent and a solvent, and the polyol contains a polyester polyol.
Citation Information
Patent Citations
Golf ball
JP1994114125A
Clear paint for golf ball, and golf ball
JP2001214131A
Golf ball
JP2013063156A
Golf ball
JP2013176530A
Dynamic Inclusion Reasoning
JP2014527222A